+0  
 
0
42
3
avatar+56 

Solve algebratically the simultaneous equations

x^2 + y^2 + 25

5x - y = 11

Here is what i did: 

-y = 11 - 5x 

-y^2 = y^2 

(-5x+11) (-5x+11) = 25^2 - 110x +121 = 25 

= x^2 -25^2 - 110x + 96 = 0

= -24^2 - 110x + 96= 0

= -12^2 - 110x + 96= 0

then i tried to factorise my answer but i can't.

 

edit: sorry my working out was -12x^2 - 55x +48 =0

YEEEEEET  Nov 11, 2017
edited by YEEEEEET  Nov 11, 2017
Sort: 

3+0 Answers

 #1
avatar+78753 
+1

x^2 + y^2 =  25    ⇒ y^2  =  25 - x^2     (1)

5x - y = 11     ⇒  5x - 11  = y     (2)

 

Square  both sides of (2)  and we have that

 

(5x - 11)^2  = y^2

 

25x^2 - 110x + 121  = y^2          set this equal to (1)

 

25x^2 - 110x + 121  =  25 - x^2     add x^2 to both sides, subtract 25 from both sides

 

26x^2 -110x + 96 = 0      divide through by 2

 

13x^2 - 55x +  48  =  0      factor as

 

(13x  - 16) (x - 3)  = 0

 

Set both factors to 0, solve for x    and we have that  x = 16/13 and x  = 3

 

So using   5x - 11  = y 

 

5(16/13) - 11 =   80/13 - 11  =  [ 80 - 143] / 13 =  -63/13

5 (3) - 11 =  15 - 11  =  4

 

So.......the solutions are  (16/13, -63/13) and ( 3, 4)

 

 

cool cool cool

CPhill  Nov 11, 2017
 #2
avatar+56 
+1

OMG after reading your solution i realised my result after first phrase should've been x^2 + 25x^2 - 110x -25 = 0 but i written -25x^2 for some reason cheeky thx 

YEEEEEET  Nov 11, 2017
 #3
avatar+1375 
0

Carelessly transposing numbers is such a frustrating habit. I have stared at many problems for prolonged periods of time without realizing such error. 

TheXSquaredFactor  Nov 12, 2017

18 Online Users

avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details